P588 A multi-site comparative study to understand sources of variability in studies of the vaginal microbiota. (14th July 2019) - Balkus, Jennifer; Proll, Sean; Holm, Johanna; Srinivasan, Sujatha; Dinwiddie, Darrell; Pol, Liam Van Der; Hoffman, Noah; Lefkowitz, Elliot; Hughes, James; Pol, Barbara Van Der; Wheeler, Cosette; Wald, Anna; et al.
Abstract : Background: The most common approach for describing bacterial communities is amplification of a taxonomically informative gene (e.g. 16S rRNA) followed by amplicon sequencing and taxonomic assignment of the sequences. Variability can arise from numerous steps in this process including DNA extraction, PCR amplification, and bioinformatics approaches for taxonomic assignment. To better understand sources of variation in describing the vaginal microbiota, we conducted a comparative study across four laboratories. Methods: A central laboratory prepared and distributed a specimen set including vaginal swabs from four women with a range of Nugent scores ( in vivo samples), three mock communities of vaginal bacteria, and positive and negative controls. For in vivo and mock communities, each laboratory was also provided specimens that underwent DNA extraction by the central laboratory. Laboratories followed their standard laboratory and bioinformatics processes. Results were analyzed by a central group blinded to laboratory. Results: For mock and in vivo communities dominated by a mix of Lactobacillus species, all laboratories successfully detected each of the taxa in the sample and reported similar relative abundances. For mock communities containing BV-associated taxa, most laboratories detected all taxa; however, some taxa, including Prevotella amnii and Atopobium vaginae, were not detected by all laboratories and there was more variation in relative abundances across the laboratories ( P. amnii relative abundance range=<1%–17%; mock community proportion of colony forming units=11%). Variations were observed between the relative abundances within laboratories compared to samples that underwent DNA extraction by the central laboratory, highlighting impact of DNA extraction method. Conclusion: Despite differences in methods, in most cases laboratories would have come to the same conclusion regarding dominant taxa in a sample, especially for Lactobacillus- dominant samples. Samples with more diverse communities had more variation in reports of minority taxa and relative abundances. Standardized use of mock communities may improve reproducibility across vaginal microbiota studies. Disclosure: No significant relationships.